An efficient dynamic access control scheme for distributed wireless sensor networks. (2018) - Chatterjee, Santanu; Roy, Sandip
In wireless sensor network (WSN) due to resource limitations, node capture attack and new node deployment, access control is essential. An access control allows neighbouring sensor nodes to authenticate each other and establish secret key for future secure communication. Most of the existing access control protocols are not secure against different active attacks also not scalable due to involvement of the base station in the new node deployment phase. In this paper, we propose a distributed dynamic access control method for large-scale WSNs. Our scheme is efficient in respect to communicational and computational overheads and also secure against all different possible known attacks. In our scheme, involvement of base station is not required during authentication and key establishment processes. Moreover, we simulate our scheme for formal security analysis using the automated validation of internet security protocols and applications (AVISPA) tool and show that our scheme is secure.